ESCASA: Analytical estimation of atomic coordinates from coarse‐grained geometry for nuclear‐magnetic‐resonance‐assisted protein structure modeling. I. Backbone and Hβ protons. Issue 22 (28th May 2021) - Lubecka, Emilia A.; Liwo, Adam
Abstract: A method for the estimation of coordinates of atoms in proteins from coarse‐grained geometry by simple analytical formulas (ESCASA), for use in nuclear‐magnetic‐resonance (NMR) data‐assisted coarse‐grained simulations of proteins is proposed. In this paper, the formulas for the backbone H α and amide (H N ) protons, and the side‐chain H β protons, given the C α ‐trace, have been derived and parameterized, by using the interproton distances calculated from a set of 140 high‐resolution non‐homologous protein structures. The mean standard deviation over all types of proton pairs in the set was 0.44 Å after fitting. Validation against a set of 41 proteins with NMR‐determined structures, which were not considered in parameterization, resulted in average standard deviation from average proton–proton distances of the NMR‐determined structures of 0.25 Å, compared to 0.21 Å obtained with the PULCHRA all‐atom‐chain reconstruction algorithm and to the 0.12 Å standard deviation of the average‐structure proton–proton distance of NMR‐determined ensembles. The formulas provide analytical forces and can, therefore, be used in coarse‐grained molecular dynamics. Abstract : Analytical expressions for approximate positions of the backbone H α and amide protons and of the side‐chain H β ‐protons in terms of α ‐carbon‐trace coordinates were proposed and parameterized for use in coarse‐grained NMR‐data‐assisted protein‐structure modeling. The expressions provide analytical forces and are thus suitable for coarse‐grained molecular dynamics.